PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DWI CIPTA USAHA, JAKARTA - Kusnita Kusnita; Sri Harini; Sudarijati Sudarijati (Jurnal Visionida, 2015)
This study aims to determine the effect of supervision and discipline of work on employee performance in PT. Dwi Cipta Usaha Jakarta. Data analysis method used is the product moment coefficient analysis to measure whether there is any relationship between variables and determination analysis to determine the percentage contribution of each variable were further tested through together and partially. Fourteen employees were taken as samples, and the results prove the supervision and discipline partial and simultaneous significant effect on the performance of employees. The results showed that more supervision than the effect on employee performance employee discipline.Keywords: Monitoring, work discipline and employee performance